Pengaruh Efektivitas Pengendalian Internal terhadap Kinerja Karyawan : Studi Kasus pada PT. Citra Niaga Logistik Cabang Maumere - Maria Ivonista; Maria Nona Dince; Pipiet Niken Aurelia (International Forum of Researchers and Lecturers, 2024)
This study aimed to determine the effect of the control environment, risk assessment process, control activities, information and communication, and monitoring on employee performance at PT. Citra Niaga Logistik Maumere branch. The research design used is descriptive quantitative associative. The population in this study were 30 employess of PT. Citra Niaga Logistik Maumere branch. Since the population is limited, this research was conducted by census or saturated sampling. Data were collected through questionnaires and analysed using descriptive and inferential statistical methods, that is multiple linear regression. Hypothesis testing was done through t test and f test. The t test results showed that partially, the control environment variables, risk assessment process, monitoring activities, information and communication, and monitoring have no significant effect on employee performance. In addition, the results of the F test showed that simultaneously, the variables of the control environment, risk assessment process, monitoring activities, information and communication, and monitoring have no significant effect on employee performance.